Paucimyces polynucleatus gen. nov, sp. nov., a novel polycentric genus of anaerobic gut fungi from the faeces of a wild blackbuck antelope. Issue 6 (23rd June 2021) - Hanafy, Radwa A.; Youssef, Noha H.; Elshahed, Mostafa S.
Abstract : The anaerobic gut fungi (AGF; phylum Neocallimastigomycota ) reside in the alimentary tracts of herbivores. Multiple novel, yet-uncultured AGF taxa have recently been identified in culture-independent diversity surveys. Here, we report on the isolation and characterization of the first representative of the RH5 lineage from faecal samples of a wild blackbuck (Indian Antelope, Antilope cervicapra ) from Sutton County, Texas, USA. The isolates displayed medium sized (2–4 mm) compact circular colonies on agar roll tubes and thin loose biofilm-like growth in liquid medium. Microscopic examination revealed monoflagellated zoospores and polycentric thalli with highly branched nucleated filamentous rhizomycelium, a growth pattern encountered in a minority of described AGF genera so far. The obtained isolates are characterized by formation of spherical vesicles at the hyphal tips from which multiple sporangia formed either directly on the spherical vesicles or at the end of sporangiophores. Phylogenetic analysis using the D1/D2 regions of the large ribosomal subunit (D1/D2 LSU) and the ribosomal internal transcribed spacer 1 (ITS1) revealed sequence similarities of 93.5 and 81.3%, respectively, to the closest cultured relatives ( Orpinomyces joyonii strain D3A (D1/D2 LSU) and Joblinomyces apicalis strain GFH681 (ITS1). Substrate utilization experiments using the type strain (BB-3 T ) demonstrated growth capabilities on a wide range of mono-, oligo- and polysaccharides, including glucose, xylose, mannose, fructose, cellobiose, sucrose, maltose, trehalose, lactose, cellulose, xylan, starch and raffinose. We propose accommodating these novel isolates in a new genus and species, for which the name Paucimyces polynucleatus gen. nov., sp. nov. is proposed.